Compliance With Point-of-Sale Tobacco Control Policies in School-Adjacent Neighborhoods in Mumbai, India. Issue 6 (July 2016) - Mistry, Ritesh; Pimple, Sharmila; Mishra, Gauravi; Gupta, Prakash C.; Pednekar, Mangesh; Ranz-Schleifer, Naomi; Shastri, Surendra
Purpose: We assessed factors associated with tobacco vendor compliance with India's Cigarettes and Other Tobacco Products Act (COTPA) provisions regulating tobacco sales and point-of-sale (POS) environments. Design: Study design was a cross-sectional random sample of tobacco vendors in Mumbai, India (2010). Setting: School-adjacent neighborhoods were the study setting. Subjects: Study subjects were tobacco vendors (n = 436). Measures: Face-to-face interviews, and audits of POS environments were used to assess compliance. Analysis: Factors associated with compliance were identified using logistic regression. Results: About 4% of vendors were fully compliant. Although 80% reported compliance with the ban on tobacco sales to minors, only 10% displayed signage about the ban. About 84% were compliant with the two–tobacco advertisement limit; of those displaying advertisements, 67% were compliant with size limits, 68% with content restrictions, and 8% with health warning requirements. Knowledge about fines for noncompliance was associated with compliance with the ban on sales to minors (odds ratio [OR], 2.12; 95% confidence interval [CI], 1.26, 3.56) and signage requirement (OR, 4.42; 95% CI, 1.76, 11.13). Greater compliance with the two-advertisement limit was associated with higher store income from tobacco (OR, .26; 95% CI, .09, .73) and lower neighborhood socioeconomic status ( p < .01); the latter was associated with advertisement size limits compliance ( p < .05). Conclusions: Compliance with COTPA provisions was low. Interventions modifying vendor knowledge about provisions and fines may increase compliance, and they should target stores that are reliant on tobacco sales.